2022
DOI: 10.3758/s13415-022-01048-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered reward processing underpins emotional apathy in dementia

Abstract: Introduction While apathy is broadly defined as a loss of motivation, it is increasingly recognised as a multidimensional syndrome spanning executive, emotional, and initiation domains. Emotional apathy is purportedly driven by deficits in using socioemotional rewards to guide behaviour, yet the link between these symptoms and reward processing, and their common neural correlates, has not been directly examined. Methods Sixty-four patients (33 behavioural-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Apathy showed the highest reported frequency in FTD including bvFTD in ten studies [ 12 , 21 , 23 , 76 82 ], while only two studies addressed PPA [ 76 , 78 ]. In studies comparing FTD with AD, FTD patients had a higher prevalence of apathy [ 12 , 21 ] and higher apathy scores [ 83 , 84 ] than AD patients. Only one study highlighted a higher prevalence of apathy in patients with bvFTD in its early stage [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apathy showed the highest reported frequency in FTD including bvFTD in ten studies [ 12 , 21 , 23 , 76 82 ], while only two studies addressed PPA [ 76 , 78 ]. In studies comparing FTD with AD, FTD patients had a higher prevalence of apathy [ 12 , 21 ] and higher apathy scores [ 83 , 84 ] than AD patients. Only one study highlighted a higher prevalence of apathy in patients with bvFTD in its early stage [ 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies used NPI [ 21 , 76 , 78 , 80 , 82 , 84 86 ], and five studies used AES [ 14 , 23 , 78 , 81 ]. One study used LARS [ 12 ], three used CBI-R [ 21 , 76 , 77 ], two used the Motivation and Energy Inventory (MEI) [ 76 , 78 ], three used the Snaith-Hamilton Pleasure Scale (SHAPS) [ 76 , 78 , 79 ], one used DAD [ 21 ], two used the Social and Emotional Assessment (Mini-SEA) [ 82 , 87 ], one used AS [ 87 ], DAS was used in four studies [ 23 , 79 , 83 , 88 ], one used the goal-directed behaviors (GDB) [ 81 ], and one used FBI [ 89 ]. Interestingly, one of the studies investigating bvFTD phenotypes related to WM changes found discordant scores on several apathy administration tests [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…This lateralization pattern has previously been reported in HD with the left striatum being predominately affected. 16,44 Further, upon examining signal alterations at an ROI level, we assessed activity disparities among distinct HDGEC subgroups (Controls vs Apathetic vs Nonapathetic). Results revealed that those categorized as apathetic exhibited especially reduced activity levels compared to both the nonapathetic and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Apathy may emerge from the impairment of any of these processes or from the inability to integrate these complex functions. [15][16][17] In the context of HD, apathy has conventionally been attributed to executive dysfunction, specifically linked with the well-documented neurodegeneration within the dorsolateral prefrontal cortex (dlPFC)-dorsal striatum loop. 11,18 However, there is a limited understanding of the involvement of limbic regions within the basal ganglia and their impact on reward processing deficits, which ultimately culminate in apathetic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A study of reward-based decision-making using the Iowa gambling task demonstrated disadvantageous decision-making profiles in those experiencing apathy (that may not be AD specific) [ 142 ]. In a study published in 2023, individuals with dementia experiencing apathy showed impaired learning in social and monetary reward conditions, indicating a relationship between social reward and emotional apathy [ 143 ] and suggesting deficits in reward-based decision-making in apathy syndrome.…”
Section: Neuropsychology Of Apathy In Admentioning
confidence: 99%